Molecular and Functional Analysis of Drosophila single-minded Larval Central Brain Expression - Freer, Stephanie M. (2011)
Developmental regulatory proteins are commonly utilized in multiple cell types throughout development. The Drosophila single-minded (sim) gene acts as master regulator of embryonic CNS midline cell development and transcription. However, it is also expressed in the brain during larval development. In this paper, we demonstrate that sim is expressed in 3 clusters of anterior central brain neurons: DAMv1/2, BAmas1/2, and TRdm and in 3 clusters of posterior central brain neurons: a subset of DPM neurons, and two previously unidentified clusters, which we term PLSC and PSC. In addition, sim is expressed in the lamina and medulla of the optic lobes. MARCM studies confirm that sim is expressed at high levels in neurons but is low or absent in neuroblasts (NBs) and ganglion mother cell (GMC) precursors. In the anterior brain, sim(+) neurons are detected in 1(st) and 2(nd) instar larvae but rapidly increase in number during the 3(rd) instar stage. To understand the regulation of sim brain transcription, 12 fragments encompassing 5’-flanking, intronic, and 3’-flanking regions were tested for the presence of enhancers that drive brain expression of a reporter gene. Three of these fragments drove expression in sim(+) brain cells, including all sim(+) neuronal clusters in the central brain and optic lobes. One fragment upstream of sim is autoregulatory and is expressed in all sim(+) brain cells. One intronic fragment drives expression in only the PSC and laminar neurons. Another downstream intronic fragment drives expression in all sim(+) brain neurons, except the PSC and lamina. Thus, together these two enhancers drive expression in all sim(+) brain neurons. Sequence analysis of existing sim mutant alleles identified 3 likely null alleles to utilize in MARCM experiments to examine sim brain function. Mutant clones of DAMv1/2 neurons revealed a consistent axonal fasciculation defect. Thus, unlike the embryonic roles of sim that control CNS midline neuron and glial formation and differentiation, postembryonic sim, instead, controls aspects of axon guidance in the brain. This resembles the roles of vertebrate Sim that have an early role in neuronal migration and a later role in axonogenesis.